2016
DOI: 10.4187/respcare.04426
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index-Dependent Ventilatory Parameters From Respiratory Inductive Plethysmography During 6-Minute Walk Test

Abstract: This respiratory monitoring method is sufficiently sensitive to point out differences between rest and exercise as well as locomotor and ventilatory differences relative to BMI during the 6MWT. Thus, this system gives useful information from the 6MWT for clinicians who want to assess respiratory patterns of patients during this commonly used test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…This finding underlines the fact that Vt obtained by RIP should be interpreted carefully. As discussed previously by Hollier et al and in our previous paper alteration of RIP values may be found in high BMI subjects (Hollier et al, 2014;Retory et al, 2016a).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…This finding underlines the fact that Vt obtained by RIP should be interpreted carefully. As discussed previously by Hollier et al and in our previous paper alteration of RIP values may be found in high BMI subjects (Hollier et al, 2014;Retory et al, 2016a).…”
Section: Discussionsupporting
confidence: 77%
“…Nevertheless, there are still some concerns regarding the reliability of RIP in obese populations. Indeed, as discussed in our previous study and by Hollier et al, there is doubt regarding adiposity's role in induction of artifacts and reduction of RIP response when measuring tidal volume in high BMI subjects (Hollier et al, 2014;Retory et al, 2016a).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…[8][9][10] In a previous study, we showed the benefits of adding information related to the 6MWT by using respiratory inductance plethysmography, with an adapted method to describe the breathing pattern in lean and overweight healthy adults during the 6MWT. 11 Hence, we hypothesized that an integrated biomechanical analysis of gait combined with ventilatory monitoring during the 6MWT in a population of overweight subjects would yield relevant biomechanical information. A description of gait pattern alteration would help describe the impact of ventilatory limitation.…”
Section: Introductionmentioning
confidence: 99%